The effect of environmental stochasticity on species richness in neutral communities. (21st November 2016) - Danino, Matan; Shnerb, Nadav M.; Azaele, Sandro; Kunin, William E.; Kessler, David A.
Abstract: Environmental stochasticity is known to be a destabilizing factor, increasing abundance fluctuations and extinction rates of populations. However, the stability of a community may benefit from the differential response of species to environmental variations due to the storage effect. This paper provides a systematic and comprehensive discussion of these two contradicting tendencies, using the metacommunity version of the recently proposed time-average neutral model of biodiversity which incorporates environmental stochasticity and demographic noise and allows for extinction and speciation. We show that the incorporation of demographic noise into the model is essential to its applicability, yielding realistic behavior of the system when fitness variations are relatively weak. The dependence of species richness on the strength of environmental stochasticity changes sign when the correlation time of the environmental variations increases. This transition marks the point at which the storage effect no longer succeeds in stabilizing the community. Abstract : Highlights: The recently proposed time-averaged neutral theory is analyzed. The effect of demographic stochasticity on the storage mechanism is examined. Unimodal effect of environmental stochasticity on species richness is explained.